Accuracy of pastoralists' memory-based kinship assignment of Ankole cattle: A microsatellite DNA analysis - Kugonza, Donald R.; Kiwuwa, G.H.; Mpairwe, D.R.; Han Jianlin; Nabasirye, M.; Okeyo Mwai, Ally; Hanotte, Olivier H. (Wiley, 2012)
This study aimed to estimate the level of relatedness within Ankole cattle herds using autosomal microsatellite markers and to assess the accuracy of relationship assignment based on farmers' memory. Eight cattle populations (four from each of two counties in Mbarara district in Uganda) were studied. Cattle in each population shared varying degrees of relatedness (first-, second- and third-degree relatives and unrelated individuals). Only memory-based kinship assignments which farmers knew with some confidence were tested in this experiment. DNA isolated from the blood of a subsample of 304 animals was analysed using 19 microsatellite markers. Average within population relatedness coefficients ranged from 0.010±0.005 (Nshaara) to 0.067±0.004 (Tayebwa). An exclusion probability of 99.9% was observed for both sire-offspring and dam-offspring relationships using the entire panel of 19 markers. Confidence from likelihood tests performed on 292 dyads showed that first-degree relatives were more easily correctly assigned by farmers than second-degree ones (p<0.01), which were also easier to assign than third-degree relatives (p<0.01). Accuracy of kinship assignment by the farmers was 91.9%±5.0 for dam-offspring dyads, 85.5%±3.4 for sire-offspring dyads, 75.6%±12.3 for half-sib and 60.0%±5.0 for grand dam-grand offspring dyads. Herd size, number of dyads assigned and length of time spent by the herder with their cattle population did not correlate with error in memorizing relationships. However, herd size strongly correlated with number of dyads assigned by the herder (r=0.967, p<0.001). Overall, we conclude that memorized records of pastoralists can be used to trace relationships and for pedigree reconstruction within Ankole cattle populations, but with the awareness that herd size constrains the number of kinship assignments remembered by the farmer.